2022
DOI: 10.3233/jad-220106
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Amyloid Curli Associated Gut Epithelial Neuroendocrine Activation Predominantly Observed in Alzheimer’s Disease Mice with Central Amyloid-β Pathology

Abstract: Background: Substantial evidence from recent research suggests an influential and underappreciated force in Alzheimer’s disease (AD) pathogenesis: the pathological signals originate from outside the brain. Pathogenic bacteria produce amyloid-like proteins “curli” that form biofilms and show functional similarities to human amyloid-β (Aβ). These proteins may contribute to neurological disease progression via signaling cascade from the gut to the brain. Objective: We propose that curli causes neuroendocrine acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Previous studies have found that stimulatory signals from the gut and vagus nerve activate the hypothalamic–pituitary–adrenal axis and promote corticosterone release ( Zimomra et al, 2011 ), leading to changes in intestinal permeability ( Moussaoui et al, 2014 ), dynamics ( Gue et al, 1991 ), and mucus ( Silva et al, 2014 ). In addition, recent studies have also revealed the importance of pathological changes in the gut-vagus-brain signaling pathway in AD ( Das et al, 2022 ). These findings further suggest a critical role for vagal signaling as a bridge between peripheral and central crosstalk.…”
Section: Crosstalk Between the Peripheral And Central Systems And Alt...mentioning
confidence: 99%
“…Previous studies have found that stimulatory signals from the gut and vagus nerve activate the hypothalamic–pituitary–adrenal axis and promote corticosterone release ( Zimomra et al, 2011 ), leading to changes in intestinal permeability ( Moussaoui et al, 2014 ), dynamics ( Gue et al, 1991 ), and mucus ( Silva et al, 2014 ). In addition, recent studies have also revealed the importance of pathological changes in the gut-vagus-brain signaling pathway in AD ( Das et al, 2022 ). These findings further suggest a critical role for vagal signaling as a bridge between peripheral and central crosstalk.…”
Section: Crosstalk Between the Peripheral And Central Systems And Alt...mentioning
confidence: 99%
“…It shows similarities to human Aβ and α-synuclein which is implicated in Parkinson's disease and may contribute to pathology through immune activation via systemic or vagal pathways ( 84 ). So far, animal experiments showed a higher abundance of Curli in AD and Parkinson's disease mouse models ( 85 , 86 ); however, substantiation of these patterns in humans is still lacking behind, particularly for AD. Immunological responses to Curli are highly site specific, provoking proinflammatory reactions in systemic infections while leading to intestinal anti-inflammatory and barrier-restoring reactions when administered orally ( 87 , 88 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we found that the integrity of the gut barrier was markedly decreased in Tg2576 AD mice which might increase bacterial amyloid (curli) burden in the gut before the appearance of Aβ deposition in the brain. 87 Curli stimulated TLR2 activation and co-localized with neuroendocrine marker PGP 9.5 within the epithelium and sub-mucosa of the gut in AD mice. 87 It indicated the vagus nerve activation by bacterial curli.…”
Section: Oxidative Stress and Inflammation In Admentioning
confidence: 94%
“… 87 Curli stimulated TLR2 activation and co-localized with neuroendocrine marker PGP 9.5 within the epithelium and sub-mucosa of the gut in AD mice. 87 It indicated the vagus nerve activation by bacterial curli. Therefore, activation of TLR2 can stimulate AD pathogenesis 87 , 88 , 92 , 102 It indicates that inhibition of TLR2 from periphery might be beneficial for AD.…”
Section: Oxidative Stress and Inflammation In Admentioning
confidence: 94%
See 1 more Smart Citation